Nonlinear dynamic modeling, identification and control of a slewing flexible structure - Góes, Luiz Carlos S.; Fenili, André; Negrão, Roberto Garcia; De Souza, Luiz Carlos Gadelha; Balthazar, José Manoel [UNESP]; De Souza Soares, Álvaro Manoel (My University, 2003)
This work deals with nonlinear dynamic modeling of a flexible slewing structure. The interaction between the slewing motion and the structure deflection has been modeled taking in account the nonlinear curvature of the flexible beam. Two different regimes of this nonlinear dynamical system are studied. Firstly, we present the numerical simulations of a nonlinear flexible beam excited near a superharmonic resonance by a prescribed harmonic angular displacement of the hub. The influence of the damping in the frequency response curves is studied and its characteristic jump phenomena investigated. Secondly, a linear approximation is used to interpret the experimental results involving modal identification and real time digital control of the slewing motion. The experimental results are compared with theoretical predictions based on constrained and unconstrained modal expansion of the slewing beam, and neglecting the nonlinear curvature effects. Copyright © 2003 by the International Astronautical Federation. All rights reserved.